The Role of All-Polyethylene Tibial Components in Modern TKA - Doran, James; Yu, Stephen; Smith, Daniel; Iorio, Richard (The Journal of Knee Surgery, 2015)
In the modern era of total knee arthroplasty (TKA), a majority of orthopedic surgeons utilize metal-backed tibial (MBT) components rather than nonmodular designs, such as all-polyethylene tibial (APT) components. Interestingly, current clinical evidence does not explain this disproportionate practice by surgeons. The shift in surgeon preference from APT to MBT components occurred in the 1980s following unfavorable results from early studies with APT. However, results from current studies that have revisited the APT versus MBT component comparison demonstrate similar implant survivorship and patient outcomes. Despite equivalent survivorship and improved cost-efficiency, APT components have not achieved equivalent utilization rates with MBT. This review of the current literature, as well as the advantages and disadvantages of APT components, will outline a rationale for the role of APT components in today's cost-driven, outcomes-oriented, patient-centered health-care system.
Keywords: total knee arthroplasty; all-polyethylene tibial components; metal-backed tibial components; bearing surfaces